IMPLEMENTATION OF FAMILY INVOLVEMENT IN EDUCATION MANAGEMENT IN THE MIDDLE SCHOOL - Lety Suharti (IKIP Siliwangi Bandung, 2021)
The development of the Family Involvement Guide model in the Implementation of Education in High School is a model that has been developed and tested by the PP-PAUD Family Education and West Java Family Education development team. This guidance model is based on the premise that the involvement of parents in senior secondary education units is deepened and extended to activities carried out in schools. The development of the Family Involvement Guide model in the Implementation of Education in high schools aims to realize active parental involvement in assisting children's education at home and at school in order to foster a character and culture of achievement. With the preparation of this model it is expected that education units, especially in senior high schools, can implement a family engagement program, including 1). Class teacher meetings with parents on the first day of school can inform the school's full profile and socialize family education programs; 2) Active parental participation in parent class activities with varied learning methods, interesting media, easy to understand, and applied; 3) Provide an overview of inspirational class activities, where parents are willing to be an inspiration; 4). Performing children's performances and creations, which showcase the interests, talents, achievements and awards of students and parents for all aspects of achievement (both academic and non-academic). The Family Involvement Model with Senior High Schools has been tested in concept at 1 School location namely SMAN 2 Cihampelas, Bandung City, and operational trials at 2 locations, namely SMA 1 Baleendah Bandung Regency and SMAN 3 Cimahi City, West Java Province. The trial was carried out for 6 months involving facilitators, parents and students in the High School education unit. This model still has many shortcomings for that improvement and refinement on this model is still being done in order to improve both the content and shape